Social democracy and social policy in neoliberal times - Deeming, Christopher (J Sociol (Melb), 2014)
This article considers the path of social policy and democracy in Australia and the latest set of welfare reforms under Labor. The reforms can be seen to mark a reaction to the excesses of neoliberal government on the one hand, but they also represent continuity in neoliberal thought and policy on the other. As we shall see, engrained ideas about individualist wage-earning welfare, that were established during the formative years of the 20th century, continue to shape, if not constrain collectivist solutions to some of the inherent social risks faced by Australian citizens today. In this light, efforts to create a welfare state geared towards meeting the needs of ‘hard-working’ Australian families appear much sharper.